2007
DOI: 10.1021/je700295e
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Differences of Halocarbon Isomers in Ionic Liquid [emim][Tf2N]

Abstract: Solubility behaviors of CFC-113 (CFCl 2 -CF 2 Cl), CFC-113a (CCl 3 -CF 3 ), CFC-114 (CF 2 Cl-CF 2 Cl), CFC-114a (CFCl 2 -CF 3 ), HCFC-123 (CHCl 2 -CF 3 ), HCFC-123a (CHClF-CF 2 Cl), HCFC-124 (CHFCl-CF 3 ), HCFC-124a (CHF 2 -CF 2 Cl), HFC-134 (CHF 2 -CHF 2 ), and HFC-134a (CH 2 F-CF 3 ) in room-temperature ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([emim][Tf 2 N]) have been investigated using a gravimetric microbalance method from (283 to 348) K or volumetric and cloud-point met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(151 citation statements)
references
References 36 publications
4
147
0
Order By: Relevance
“…[13] b Ref. [14] have been successfully applied for refrigerant/lubricant oil mixtures [16,17], and various hydrofluorocarbons, NH 3 , and CO 2 mixtures with ionic liquids [18][19][20][21][22][23][24][25][26][27]. We have also successfully modeled ternary systems of CO 2 [14].…”
Section: Binary Vlle Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] b Ref. [14] have been successfully applied for refrigerant/lubricant oil mixtures [16,17], and various hydrofluorocarbons, NH 3 , and CO 2 mixtures with ionic liquids [18][19][20][21][22][23][24][25][26][27]. We have also successfully modeled ternary systems of CO 2 [14].…”
Section: Binary Vlle Measurementsmentioning
confidence: 99%
“…We model the phase behavior using our well established cubic equation-of-state (EOS) method [16][17][18][19][20][21][22][23][24][25][26][27] and show that the N 2 O (and CO 2 ) binary systems demonstrate both Type III and Type V phase behavior [11,12]. In addition, Henry's law constants for the present systems are analyzed and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the effect of the anion, three ILs were compared based on the cation 1-hexyl-3-metyl-imidazolium ( 4,9 This trend scales with the diameter of the anion or charge density as larger anions can have more disperse negative charge. Ions with more disperse charge can be more readily solvated by the polar compressed hydrofluorocarbon, and thus become miscible at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Shiflett et al, [6][7][8][9] have reported the majority of known data. They have measured the low-pressure (\10 bar) vapor-liquid equilibrium (VLE) and vapor-liquid-liquid equilibrium (VLLE) data of a large series of refrigerants and ILs; see Shiflett and Yokozeki 9 and Ren et al 10 14 …”
Section: Ionic Liquids/refrigerantsmentioning
confidence: 99%
“…For an analogous series of 1,2,4-triazolium-based ILs, miscibility data have been reported only for common organic solvents [19,20]. Phase equilibria between the common hydrophobic IL 1-ethyl-3-methyl-imidazolium triflimide and HFE [21], halocarbon isomers [22], and (refrigerant) fluorocarbons [23,24] have been studied, revealing large differences in the solubilities. Based on this unique phase behavior of fluorocarbons in RTILs, they have been proposed as extractants for separation and purification.…”
Section: Introductionmentioning
confidence: 99%